Безпека виконання монтажних робіт під час експлуатації електроінструменту класу ІІІ - Юрченко, Олександр Юрійович; Yurchenko, Oleksandr; Барсукова, Ганна Володимирівна; Barsukova, Hanna (Запоріжжя: ТДАТУ, 2025)
UA: Використання електроінструменту класу ІІІ за умовами електробезпеки є найбільш надійним способом виконання механізованих робіт в електроустановках. Перевагами використання такого електроін-струменту є його автономність через наявність свого незалежного джерела живлення безпечної наднизької напруги, а також безпека – через унеможливлення проявів дії електричного струму на стан здоров’я людини. Серед заходів, спрямованих на забезпечення належного рівня безпеки для персоналу, згідно з другим аспектом безпеки, є використання засобів індивідуального захисту, спрямованих на убезпечення персоналу від нега-тивної дії рухомих робочих органів електроінструменту. Тому ефективність використання електроінструменту класу ІІІ підтверджено з погляду як надійності та якості виконання робіт в електроустановках, що не поступа-ються електроінструменту класів І та ІІ, так і рівня безпеки з погляду безпеки ураження електричним струмом. /// EN: The use of class III power tools according to electrical safety conditions is the most reliable way to perform mechanized work in electrical installations. The advantages of using such a power tool are its autonomy due to the presence of its own independent power source of safe extra-low voltage, as well as safety in terms of preventing the effects of electric current on human health. Among the measures aimed at ensuring an adequate level of safety for personnel, according to the second aspect of safety, is the use of personal protective equipment aimed at protecting personnel from the negative effects of moving working parts of the power tool. Therefore, the effectiveness of using class III power tools has been confirmed in terms of both reliability and quality of work in electrical installations, which are not inferior to class I and II power tools, as well as the level of safety in terms of safety from electric shock. Using batteries as a power source is a fairly effective solution, which immediately gives several advantages. Autonomy and safety make this tool popular among modern installers. Due to the use of the specified tool, safety measures are reduced to equipping personnel exclusively with personal protective equipment against noise, dust, chips and various rotating working parts of the tool, and the danger of electric shock is eliminated by using safe extra-low voltage as a power source for the electrified tool. By comparing the measures regulated by the Rules for the safe operation of consumer electrical installations, in particular the reliable fastening of working parts and materials to be processed, as well as personal protective equipment when working with power tools with moving, rotating parts, it is possible to implement safe working conditions for personnel in electrical installations with a battery-powered power tool that is safe to use from the point of view of classifying it as a class III power tool.
Safety in installing work when using class III power tools
Keywords: техніка безпеки; безпека праці; монтаж; електроінструмент; безпечна наднизька напруга; ПБЕ; електрична енергія; джерело електричної енергії; технічна експлуатація; safety; occupational safety; installation; power tools; safe extra-low voltage; PBE; electric energy; source of electric energy; technical operation